Exploring the potential use of melatonin as a modulator of tramadol-induced rewarding effects in rats - Hakami, Alqassem Y.; Alghamdi, Badrah S.; Alshehri, Fahad S. (Frontiers in Pharmacology, 2024)
Background: Melatonin is responsible for regulating the sleep-wake cycle and circadian rhythms in mammals. Tramadol, a synthetic opioid analgesic, is used to manage moderate to severe pain but has a high potential for abuse and dependence. Studies have shown that melatonin could be a potential modulator to reduce tramadol addiction. Methods: Male Wistar rats were used to investigate the effect of melatonin on tramadol-induced place preference. The rats were divided into four groups: control, tramadol, tramadol + melatonin (single dose), and tramadol + melatonin (repeated doses). Tramadol was administered intraperitoneally at 40 mg/kg, while melatonin was administered at 50 mg/kg for both the single dose and repeated-dose groups. The study consisted of two phases: habituation and acquisition. Results: Tramadol administration produced conditioned place preference (CPP) in rats, indicating rewarding effects. However, melatonin administration blocked tramadol-induced CPP. Surprisingly, repeated doses of melatonin were ineffective and did not reduce the expression of CPP compared to that of the single dose administration. Conclusion: The study suggests that melatonin may be a potential therapeutic option for treating tramadol addiction. The results indicate that melatonin attenuates the expression of tramadol-induced CPP, supporting its uses as an adjunct therapy for managing tramadol addiction. However, further studies are needed to investigate its effectiveness in humans.